PENGARUH KEPEMIMPINAN, HUBUNGAN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP DISIPLIN KERJA KARYAWAN - Sugiantara, I Wayan; Ardana, I Komang (E-Jurnal Manajemen, 2019)
Business competition in the field of tourism accommodation causes corporate leaders and employees, especially lodging places, are required to always act professionally. The purpose of this study are (1) to determine the leadership style, work relationship and physical work environment simultaneously have a significant effect on employee work discipline, (2) to know the leadership style, work relationship and physical work environment partially have a significant effect on employee work discipline , (3) to find out the leadership style, work relationship and physical work environment dominantly have a significant influence on employee work discipline. This research was conducted in Alam Kulkul Boutique Resort Kuta-Bali which is engaged in tourism accommodation using census method (total sampling) in determining a sample of 65 respondents, through multiple linear regression analysis techniques. The results of the analysis prove that leadership, work relationships and physical work environment simultaneously have a positive and significant effect on employee work discipline. Leadership, work relations and physical work environment partially have a positive and significant effect on employee work discipline. The work environment has a dominant and significant positive effect on employee work discipline. Keywords : leadership, work relationships, physical work environment and work discipline